Pengaruh Pengelolaan Ekonomi Produktif dalam Mengentaskan Kemiskinan di Kota Lumajang Studi pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Lumajang - Izzah Masruroh; Muhammad Farid (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
This study discusses the effect of productive economic management in the National Zakat Agency (BAZNAS) of Lumajang Regency. The background of the study is the management system of zakat, infaq and shadaqah distribution in Indonesia, there are two categories, namely, consumptively and productively. However, the pattern of giving so far is generally consumptive. But in its development the ZIS distribution system was innovated in order to maximize the utilization of ZIS funds to achieve the desired goals in Islam, one of which is the productive distribution of ZIS namely Productive Economy. Productive distribution of ZIS is expected to empower poor mustahiq to accelerate poverty reduction by providing access to business capital in a rolling manner. The formulation of the problem in this study are: 1. Does the management of the productive economy in BAZNAS Lumajang Regency affect poverty alleviation. The objectives of this study are: 1. To find out the empirical evidence of the effect of productive economic management in alleviating poverty in the city of Lumajang. This research uses quantitative methods, with a field research approach. Data collection techniques using questionnaires, interviews, observation, and documentation. The data analysis uses a simple regression statistical tool. The results of this study indicate that there is a positive and significant influence between productive economic management on poverty alleviation in Lumajang city with R2 = 0.6739, which indicates that 67.39% of poverty reduction variables can be influenced by productive zakat management variables, while 32.61 The remaining% is influenced by other variables not included in the simple regression model. Keywords: Productive Economy Management, Poverty Alleviation.